Gut Microbiota Shapes the Efficiency of Cancer Therapy - Ma, Weidong; Mao, Qixing; Xia, Wenjie; Dong, Gaochao; Yu, Changhua; Jiang, Feng (Frontiers in Microbiology, 2019)
Systems biology provides an opportunity to discover the role that gut microbiota play in almost all aspects of human health. Existing evidence supports the hypothesis that gut microbiota is closely related to the pharmacological effects of chemical therapy and novel targeted immunotherapy. Gut microbiota shapes the efficiency of drugs through several key mechanisms: metabolism, immunomodulation, translocation, enzymatic degradation, reduction of diversity, and ecological variability. Therefore, gut microbiota have emerged as a novel target to enhance the efficacy and reduce the toxicity and adverse effects of cancer therapy. There is growing evidence to show that cancer therapy perturbs the host immune response and results in dysbiosis of the immune system, which then influences the efficiency of the therapy. Studies suggest that gut microbes play a significant role in cancer therapy by modulating drug efficacy, abolishing the anticancer effect, and mediating toxicity. In this review, we outline the role of gut microbiota in modulating cancer therapy and the implications for improving the efficacy of chemotherapy and immunotherapy in clinical practice. We also summarize the current limitations of the safety and effectiveness of probiotics in cancer therapies such as personalized cancer therapy.